Implementation of an Android Mobile Application-Based Payment System for Avicenna Integrated Islamic Elementary School Bekasi - Nuning Khanif Aulia (Asosiasi Dosen Muda Indonesia, 2026)
The manual school payment system creates quite long queues and does not create time efficiency. Parents of students are required to come to school, especially to the Administration section because the system is still manual. This research was conducted at a Private Elementary School in Bekasi City. The split payment system makes many parents confused and often scattered. Every month there are several fees that parents must pay at this school. Tuition fees, Parent Teacher Association (POMG), Teaching and Learning Activities (KBM), and Books. It is hoped that this research will make it easier for parents so that the financial system in the school can run well and according to expectations. Then there is no longer a long queue system because the administration counter is only filled by 1 school employee. So that every parent can make school payments in real time, 24 hours whenever and wherever just by accessing this application. Of course, this payment application works with a bank in collaboration with the school foundation.